The fragmentation pathways of azaspiracids elucidated using positive nanospray hybrid quadrupole time-of-flight (QqTOF) mass spectrometry. Issue 2 (2004) - Hamilton Hamilton, Brett Brett; Díaz Sierra Díaz Sierra, Mónica Mónica; Lehane Lehane, Mary Mary; Furey Furey, Ambrose Ambrose; James James, Kevin J. Kevin J.
Abstract : The azaspiracids, AZA1, AZA2 and AZA3, are the predominant shellfish toxins responsible for the human toxic syndrome, azaspiracid poisoning. Collision induced dissociation (CID) mass spectra were generated for azaspiracids using nano-electrospray ionisation (ESI) with a hybrid quadrupole time-of-flight (QqTOF) mass spectrometer in positive mode. Six main backbone fragmentations of the polyether skeleton of azaspiracids were observed as well as multiple neutral losses of water molecules from the parent and product ions. The characteristic charge-remote fragmentation of the carbon skeleton of azaspiracids produced nitrogenous ions. The three azaspiracids differ from one another by 14 Da due to methylation in the A- and E-rings. Three fragmentation pathways, involving cleavage of the E-ring, C27–C28 and G-ring, gave ions that were common to all azaspiracids. Another three fragmentations involving the A-ring, C-ring and C19–C20, were useful for distinguishing between azaspiracid analogues. Multiple tandem ion‒trap mass spectrometry (MS n ) was used to confirm the fragmentation pathways.